The Attitudes of Muslims Towards Muslim Women In Prisons - Abdul Aziz Shamhuna (Penerbit Hellow Pustaka, 2024)
The Prisons across the world are meant to serve the interest of the human society. This is to help the society punish its non-law abiding citizens. In the early societies the believed in revenge, torture, the removal of offenders from the midst of ‘good people’ and even execution were common. As civilization occurs, the idea of punishment, torture and even execution have been substituted with reform and transformation. This change was important by the rights of prisoners instituted by the United Nations. Base on the above information, the conditions of many prisons in Ghana as well as the prisoners are nothing to write home about. Prisoners’ rights and freedoms are always infringed upon of which Muslim Women Prisoners are most often the victims. This article sought to find out the attitudes of Muslims towards Muslim Women in the Prisons. It was among the main objectives of the work to find out, the attitudes of Muslims towards Muslim women in the Prisons, whether the Muslim women were accorded the right respect in society, especially after serving their prison terms, right to practice their religion, whether there was any religious education available to the Muslim women in the prisons, and find the general conditions in the Prisons. The work used qualitative methods. Questionnaires were administered to the Muslim women prisoners, Muslims, Islamic Scholars and Prison officers, in order to gather the data. The data was afterward analyzed. After the research, it was realized that Muslim women in the prisons had the chance to practice their religious duties. They also had religious education as well as visiting scholars. The conditions of the prisons were very bad and the inmates had insufficient food, water and medical care.